Characterization of the Polypeptides Formed in Response to Encephalomyocarditis Virus Ribonucleic Acid in a Cell-Free System from Mouse Ascites Tumor Cells - Kerr, Ian M. (1972)
The polypeptide products synthesized at different times in a cell-free system from Krebs mouse ascites tumor cells in response to the addition of encephalomyocarditis (EMC) virus ribonucleic acid (RNA) were characterized by electrophoresis on polyacrylamide gels and fingerprint analysis of their tryptic peptides. Translation of the EMC RNA genome with time occurred in a nonrandom fashion in these systems, to yield products containing sequences characteristic of both virion capsid polypeptides and EMC-specific polypeptides present only in the infected cell. The molecular weights of the products fell in a series from 20,000 to 140,000 daltons, although occasionally traces of larger polypeptides were also observed. All of the major polypeptides appeared to arise from partial or complete translation of about 60% of the EMC RNA genome. They were not formed by cleavage of a large precursor molecule. It is suggested that they are artifacts generated by premature “termination” of nascent polypeptide chains at preferred sites.